Saturated fat in an evolutionary context - Eirik Garnås (Lipids in Health and Disease)
Abstract Evolutionary perspectives have yielded profound insights in health and medical sciences. A fundamental recognition is that modern diet and lifestyle practices are mismatched with the human physiological constitution, shaped over eons in response to environmental selective pressures. This Darwinian angle can help illuminate and resolve issues in nutrition, including the contentious issue of fat consumption. In the present paper, the intake of saturated fat in ancestral and contemporary dietary settings is discussed. It is shown that while saturated fatty acids have been consumed by human ancestors across time and space, they do not feature dominantly in the diets of hunter-gatherers or projected nutritional inputs of genetic accommodation. A higher intake of high-fat dairy and meat products produces a divergent fatty acid profile that can increase the risk of cardiovascular and inflammatory disease and decrease the overall satiating-, antioxidant-, and nutrient capacity of the diet. By prioritizing fiber-rich and micronutrient-dense foods, as well as items with a higher proportion of unsaturated fatty acids, and in particular the long-chain polyunsaturated omega-3 fatty acids, a nutritional profile that is better aligned with that of wild and natural diets is achieved. This would help prevent the burdening diseases of civilization, including heart disease, cancer, and neurodegenerative conditions. Saturated fat is a natural part of a balanced diet; however, caution is warranted in a food environment that differs markedly from the one to which we are adapted.